All-solid-state AlGaN/GaN-based ion-sensitive heterostructure field effect transistor pH sensor microprobe encapsulated in medical needle - Fengge Wang; Minjie Zhang; Honghui Liu; Yanyan Xu; Zhiwen Liang; Junyu Shen; Zhengwen Xiao; Chaokun Yan; Zhisheng Wu; Yang Liu; Baijun Zhang (AIP Advances, 2022)
It is very important to monitor pH values. In this paper, we fabricated an all-solid-state AlGaN/GaN-based ion-sensitive heterostructure field effect transistor (ISHFET) pH sensor microprobe. The microprobe could facilitate measurement of pH values. The microprobe was fabricated by packaging the pH sensor microprobe chip into a 21 G medical needle. The performance of the integrated pH sensor microprobe was evaluated in pH range of 4–9.18. A sensitivity of 143.57 µA/pH can be achieved using the pH sensor microprobe with a width to length ratio of 4.2 at a drain–source voltage of 0.5 V. The pH sensor microprobe keeps a similar current when the pH values of solutions are the same. A response time of 1 s can be achieved when no neutralization reaction occurs. The pH sensor microprobe can accurately measure pH of solutions under 0.1M interfering ions. This probe-type AlGaN/GaN-based ISHFET pH sensor may be used in medicine or biology, especially in the detection of pH of biological fluid, blood, and some precious biological samples.